Democratic Republic of the Congo : Poverty Reduction Strategy Paper. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Poverty Reduction Strategy Paper on the Democratic Republic of Congo discusses economic policies and development. The macroeconomic and budget framework has been developed to take into account the effects of sectoral policies to maintain macroeconomic stability, a necessary condition for laying the foundation of economic growth and poverty reduction. It is based on the profile of public spending, the assessment of costs for achieving the Millennium Development Goals by 2020, and the sector-based economic growth theories taking into account the uncertainties of the international environment and the real potential of the Congolese economy. It is found that it allows for a realistic programming of public spending while highlighting the main budgetary choices proposed by the government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet